Comparison of Tibial Plateau technique Leveling Osteotomy - TPLO with and without the use of the jig, in the treatment of cranial cruciate ligament rupture - clinical study in dogs - Ramos, Renato Moura (2012)
ABSTRACT. Ramos R.M., Atallah F.A., Luz M.J., Hyppolito W.C., Vale D.F., Scheffer J.P., Silva R.S. & Oliveira A.L.A. [Comparison of Tibial Plateau technique Leveling Osteotomy - TPLO with and without the use of the jig, in the treatment of cranial cruciate ligament rupture - clinical study in dogs]. Comparação da técnica de Tibial Plateau Leveling Osteotomy - TPLO com e sem o uso da jig, no tratamento da ruptura do ligamento cruzado cranial - Estudo clinico em cães. Revista Brasileira de Medicina Veterinária, 25(Supl.1):21-29, 2013. Curso de Pós-Graduação em Ciência Animal, Universidade Estadual do Norte Fluminense Darcy Ribeiro, Avenida Alberto Lamego, 2000, Parque Califórnia, Campos dos Goytacazes, RJ 28013602, Brasil. Email: renatomoran@hotmail.com The cranial cruciate ligament failure (CCLR) is one of the most orthopedic abnormalities found in the knees of dogs of any age or size, being the most common cause of lameness of the hind limbs of these. Origin of the rupture of the LCC can be traumatic and / or degenerative. Diagnosis is based primarily on cranial “drawer” tests and the tibial compression test. Treatment may be medical or surgical. Surgical treatment is divided into techniques extracapsular, intracapsular and corrective osteotomies. The goal of this study was to compare the postoperative outcomes from technique Tibial Plateau Leveling Osteotomy - TPLO, with and without the use of the jig. Conclusion: Do not use the jig decreased surgery time and tissue injury. Clinical results postoperative were the same for both groups. In this experiment conditions, the jig was unnecessary to perform the TPLO.